BUILDING THE FUTURE OF EDUCATION: DEFINITIONS AND CONCEPTS OF EDUCATION MANAGEMENT - Idrus, Sulkifli; Nurrahma; Muh. Resky Ananda Andri; Fadil khaer (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang (UIN) Raden Fatah Palembang, 2025)
This study aims to examine the definition and basic concepts of educational management and the application of its principles in the implementation of education, particularly in efforts to improve the quality of education in secondary education institutions. Educational management principles such as efficiency, effectiveness, participation, accountability, and transparency are analyzed through a literature review using a descriptive qualitative approach. Data were obtained from various relevant literature sources, including books, journal articles, and policy and institutional documents. The results of the study indicate that the consistent application of educational management principles can improve the efficiency of resource management, strengthen school governance, and encourage stakeholder involvement in the educational process. Furthermore, this study emphasizes the importance of educational management as a systemic framework in creating quality, adaptive, and sustainability-oriented educational institutions. These findings are expected to serve as a conceptual foundation for policy formulation and the development of managerial practices in Islamic and general educational institutions.